The developing of the system of equations of real blades surfaces and the algorithm for predicting the gas turbine engines blisks normed precision factors - Тернюк, Игорь Александрович (Technology audit and production reserves, 2016)
The article is devoted to the developing of the system of equations of real blades surfaces and the algorithm for predicting the gas turbine engines BLISKs normed precision factors. The main aim is receiving the dependencies and the sequence of its utilizing, what is necessary to resolve the product precision predicting and control problems. The assumption, that blades surfaces normed errors are determined by groups of the accessible for control factors: geometrical, kinematic, thermal, force and deterioration was used in the capacity of base idea. These factors are reduced to twenty four reduced primary errors. This has made it possible to obtain the required differential and integral system of matrix equations which reflects the relation between real blade surface radius-vector and above mentioned errors. The radius-vector increment was used as argument in the dependencies for calculating the normed precision factors. Model adequacy was reinforced by the conducted experiments. The obtained system of equations of the real blades surfaces and algorithm for calculating the gas turbine engines BLISKS normed precision factors are applicable for resolving retrieval and project problems, which are connected with product precision increase reserves identification and optimal providing of the precision demands during BLISKS machining technological processes designing. It is the base for creating CAM-systems in the domain of aviation engines manufacturing.